ALCAM Mediates DC Migration Through Afferent Lymphatics and Promotes Allospecific Immune Reactions - Willrodt, Ann-Helen; Salabarria, Ann-Charlott; Schineis, Philipp; Ignatova, Desislava; Hunter, Morgan Campbell; Vranova, Martina; Golding-Ochsenbein, Alexandra M.; Sigmund, Elena; Romagna, Annatina; Strassberger, Verena; Fabbi, Marina; Ferrini, Silvano; et al. (Frontiers in Immunology, 2019)
Activated leukocyte is cell adhesion molecule (ALCAM, CD166) is a cell adhesion molecule of the immunoglobulin superfamily and has been implicated in diverse pathophysiological processes including T cell activation, leukocyte trafficking, and (lymph)angiogenesis. However, exploring the therapeutic potential of ALCAM blockade in vivo has been difficult due to the lack of antibodies with blocking activity towards murine ALCAM. In this study, we identified and characterized a monoclonal antibody with high affinity and specificity for murine ALCAM. This antibody reduced in vitro T cell activation induced by antigen-presenting dendritic cells (DCs) as well as (trans)migration of murine DCs across lymphatic endothelial monolayers. Moreover, it reduced emigration of DCs from in vitro-cultured human skin biopsies. Similarly, antibody-based blockade of ALCAM reduced (lymph)angiogenic processes in vitro and decreased developmental lymphangiogenesis in vivo to levels observed in ALCAM-deficient mice. Since corneal allograft rejection is an important medical condition that also involves (lymph)angiogenesis, DC migration and T cell activation, we investigated the therapeutic potential of ALCAM blockade in murine corneal disease. Blocking ALCAM lead to DC retention in corneas and effectively prevented corneal allograft rejection. Considering that we also detected ALCAM expression in human corneal DCs and lymphatics, our findings identify ALCAM as a potential novel therapeutic target in human corneal allograft rejection.